Revitalizing reproductive health: innovations and future frontiers in restorative medicine - Francesco Maria Bulletti; Evaldo Giacomucci; Maurizio Guido; Antonio Palagiano; Maria Elisabetta Coccia; Carlo Bulletti (Therapeutic Advances in Reproductive Health)
Background: Infertility affects around 17.5% of reproductive-aged individuals worldwide, posing significant personal and public health challenges. Although Medically Assisted Reproduction and Assisted Reproductive Technology (ART; e.g., in vitro fertilization) have advanced outcomes, many couples fail to conceive due to unaddressed pelvic, uterine, or systemic factors. Objectives: We aim to (1) define the current usage of Restorative Reproduction Medicine (RRM) in clinical practice, (2) compare RRM outcomes with conventional ART, and (3) propose an integrated model of RRM plus ART for optimal fertility care. Design: A systematic review following PRISMA guidelines was conducted (INPLASY registration no. INPLASY2024110069). Data sources and methods: We searched PubMed, Scopus, and Web of Science (January 1995–October 2024), combining terms such as “restorative reproductive medicine,” “intrauterine adhesions,” “myomas,” “polyps,” “hydrosalpinx,” “endometritis,” “BMI,” “thyroid dysfunction,” “microbiome,” and “assisted reproductive technology.” Inclusion criteria: studies on uterine/systemic factors affecting infertility, focusing on surgical/pharmacological RRM interventions and ART limitations. Exclusion criteria: male-only infertility, case reports, narrative reviews, non-English publications. Quality assessment employed the Newcastle-Ottawa Scale and the Cochrane Risk of Bias Tool. We also briefly noted potential publication bias due to language and study-type restrictions. Results: From >25,000 initial titles, 3 sequential screenings yielded 145 key articles addressing uterine (septum, myomas, polyps, adhesions) and systemic (body mass index (BMI) extremes, thyroid dysfunction, microbiome imbalance) factors. Surgical corrections (e.g., hysteroscopic removal of polyps/myomas, salpingectomy for hydrosalpinx) significantly improved natural conception and ART success (⩾20%–40% increase in clinical pregnancy). Chronic endometritis treatment, endometrial microbiome modulation, and BMI/thyroid optimization further improved pregnancy rates by 15%–20%. Comparisons of RRM versus ART alone indicated that RRM often lowers overall cost and may reduce miscarriage, while ART offers immediate embryo transfer. Combining RRM to correct pathologies prior to ART can boost implantation and live birth rates (⩾40%–70% improvement in some studies). Conclusion: Restorative Reproductive Medicine comprehensively addresses pelvic and systemic abnormalities, thereby enhancing fertility outcomes and complementing ART. A proposed integrated model—RRM diagnostics/interventions followed by ART if needed—maximizes success, reduces time/cost, and emphasizes holistic reproductive health. Further multicenter trials are warranted to standardize protocols and fully realize RRM’s potential in modern fertility care.